Hubungan Tingkat Kosmopolitan dan Karakteristik Inovasi dengan Sikap Peternak Sapi Potong pada Pengobatan Luka Traumatik Menggunakan Salep Ekstrak Tanaman Yodium - Budi Purwo Widiarso; Chichika Jeni; Nurdayati Nurdayati (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
The research was conducted in Mangunrejo Village, Tegalrejo District, Magelang Regency. The purpose of the study was to determine the relationship between the level of cosmopolitan and innovation characteristics with the attitude of beef cattle breeders, in the treatment of traumatic wounds using Iodine plant extract ointment. Data were collected by means of observation and questionnaires. The variables observed were the level of cosmopolitan, innovation characteristics and attitudes. The study design used is the One Shot Case Study method. The population used is the Amanah farmer/livestock group with a sample of 32 people determined using the saturated sample technique. Analysis of the data used is descriptive analysis and statistical analysis (simple correlation or Pearson product moment and multiple correlation). The results showed a significant relationship (p < 0.05) between the cosmopolitan level and the attitude of goat breeders with a correlation coefficient (ryx1) of 0.395 (positive), indicating a significant relationship (p < 0.05) between the characteristics of innovation and the attitudes of cattle farmers. cut on the treatment of traumatic wounds using an iodine plant extract ointment and the correlation coefficient (ryx2)= 0.355 (positive). Taken together, there was also a significant relationship (p < 0.05) between the level of cosmopolitan and innovation characteristics with the attitude of beef cattle farmers on the treatment of traumatic wounds using plant extract ointment (Ryx1x2) of 0.473 (positive). This study can be concluded that there is a relationship between the level of cosmopolitan and innovation characteristics with the attitude of beef cattle farmers in the treatment of traumatic wounds using plant extract ointment.